Regression of isoproterenol-induced cardiac hypertrophy by Na+/H+ exchanger inhibition - Ennis, Irene Lucía (2003)
Cardiac hypertrophy is often associated with an increased sympathetic drive, and both in vitro and in vivo studies have demonstrated the development of cardiomyocyte hypertrophy in response to either α- or β-adrenergic stimulation. Because an association between the Na+/H+ exchanger and cellular growth has been proposed, this study aimed to analyze the possible role of the antiporter in isoproterenol-induced cardiac hypertrophy. Isoproterenol alone (5 mg/kg IP once daily) or combined with a selective inhibitor of the Na+/H+ exchanger activity (3 mg · kg-1 · d-1 BIIB723) was given to male Wistar rats for 30 days. Sex- and age-matched rats that received 0.9% saline IP daily served as controls. Echocardiographic follow-up showed a 33% increase in left ventricular mass in the isoproterenol-treated group, whereas it did not increase in the isoproterenol+BIIB723-treated group. Heart weight-to-body weight ratio at necropsy was 2.44 ± 0.11 in controls and increased to 3.35 ± 0.10 (P < 0.05) with isoproterenol, an effect that was markedly attenuated by BIIB723 (2.82 ± 0.07). Intense cardiomyocyte enlargement and severe subendocardial fibrosis were found in isoproterenol-treated rats, and both effects were attenuated by BIIB723. Myocardial Na+/H+ exchanger activity and protein expression significantly increased in isoproterenol-treated rats compared with the control group (1.45 ± 0.11 vs 0.91 ± 0.05 arbitrary units, P < 0.05). This effect was significantly reduced by BIIB723 (1.17 ± 0.02, P < 0.05). In conclusion, our results show that Na+/H+ exchanger inhibition prevented the development of isoproterenol-induced hypertrophy and fibrosis, providing strong evidence in favor of a key role played by the antiporter in this model of cardiac hypertrophy.